2020
DOI: 10.3390/s20082331
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Significant Individual Historical Factors of Driving Risk Using Hierarchical Clustering Analysis and Quasi-Poisson Regression Model

Abstract: Driving risk varies substantially according to many factors related to the driven vehicle, environmental conditions, and drivers. This study explores the contributing historical factors of driving risk with hierarchical clustering analysis and the quasi-Poisson regression model. The dataset of the study was collected from two sources: naturalistic driving experiments and self-reports. The drivers who participated in the naturalistic driving experiment were categorized into four risk groups according to their n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Seacrist et al [27] utilized naturalistic driving data to compare and analyze the frequency and characteristics of a high-risk driver's near-crashes. Naji et al [4,28] adopted two logit regression models to explore the affecting factors of driving risk on near-crashes and individual drivers. Perez adopted a method for identifying and validating near-crash events using different kinematic thresholds [29].…”
Section: Related Workmentioning
confidence: 99%
“…Seacrist et al [27] utilized naturalistic driving data to compare and analyze the frequency and characteristics of a high-risk driver's near-crashes. Naji et al [4,28] adopted two logit regression models to explore the affecting factors of driving risk on near-crashes and individual drivers. Perez adopted a method for identifying and validating near-crash events using different kinematic thresholds [29].…”
Section: Related Workmentioning
confidence: 99%
“…In other related studies [48][49][50], Poisson regression models were fitted for RTF data with the basic assumption that the data produced same mean and variance. However, Shaik and Hossain [51] faulted the use of the Poisson regression model, as the underlying assumptions are difficult to satisfy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jiho Lee et al proposed a hierarchical clustering analysis algorithm to construct a learner emotion analysis model for learning experience text and classi ed learners through hierarchies. us, the emotion analysis of each learner is realized [7,8]. Agnivesh et al applied clustering algorithm to data classi cation, which showed good performance and e ect [9].…”
Section: Related Workmentioning
confidence: 99%